Semi-Strong Form of Market Efficiency : Does all Critical Information Affect Stock Price Valuations? - Deshpande, Rajesh (Indian Journal of Research in Capital Markets, 2017)
Information about company fundamentals, among many things, should determine the prices of stocks. Usually, financial markets operating under a semi strong efficient market (SSEM) hypothesis imply that market prices of equity scrips react to business and environmental information which is available in the public domain. However, the paper established that even though SSEM hypothesis may hold most of the time, all publicly available data may not necessarily be factored to buy or sell stocks. There could be instances where some critical information (say, ratios of business efficiency), which is publicly available, may not be considered in favour of more directly observed or easily derived piece of information, that is, sales or profits. The paper studied correlation of business aggressiveness or strategic intent (expenditure made by the business to improve its competitive position) and historical market value to book value ratio of select scrips. Evidence emanating from the study indicated that vital information, which may affect business performance, in many cases was ignored by the market while deriving stock prices. The paper also proposed a non-econometric technique to assess company fundamentals which could lead to assessing stocks which were likely to improve their valuations in the mid-term (1-2 years horizon). The study concerned five IT stocks listed on the BSE to examine whether market to book valuation behaved in some accordance with the firm's strategic intent (measured as business expenditure, that is, employee cost as a % of sales).